Analysis of Factors Associated with Work Stress on Teachers of Special Needs School - Nadya Admirelia Masan; Luh Putu Ruliati; Ribka Limbu (Universitas Nusa Cendana, 2022)
Stress is a condition that emerges from human and occupational interaction and is marked by human changes that force them to deviate from their normal function. Stress does not just happen but can be triggered by some factors, which are individual factors, organizational factors (job demands, social support, work roles), and environmental factors (work climates, noise). This study aims to find out factors related to work stress for SLB Pembina of Kupang city. The research is a type of analytic observational study with a cross-sectional view. Data collection is done with an interview technique. There are 50 teachers with a total sample of 45 teachers from Special School Pembina of Kupang city. The responders were obtained by the simple random sampling method. Data analysis uses the chi-square test with prosperity (0,05). Studies have found that job demands have a significant relationship with work stress with p-value = 0,003, social support has a significant relationship with work stress with p-value=0,000, the working role has a significant relationship with work stress with p-value = 0,000, and the working climate has a significant relationship with work stress with p-value = 0,009.